Democratic Governance and Human Rights in the Digital Age - Hoang Minh, Le Thi; Giao, Vu Cong (VNU Journal of Science: Legal Studies; Vol 40 No 3DO - 10.25073/2588-1167/vnuls.4600, 2024)
The article analyzes the concepts of the digital era, democratic governance, human rights and the relationship between these categories. On that basis, it focuses on analyzing the positive and negative impacts of the digital era on democratic governance and the safeguarding and advancement of human rights. In addition, it proffers a series of pragmatic solutions aimed at harnessing the potential benefits of this digital age, as well as effectively addressing the challenges posed to democratic governance and human rights within the digital landscape. According to the authors, it is necessary to clearly understand the power and versatile nature of digital technology, which refers to its ability to be used for various purposes and its adaptability to different contexts. By understanding this, we can identify comprehensive and synchronous strategies and solutions to ensure that digital technology is used effectively and responsibly by all subjects, thereby both enhancing democratic governance and the level of enjoyment of human rights and preventing abuses of power and violations of human rights through digital technology.